Do Study Skills Matter More than Gender? The Impact of Academic Self-Efficacy on Students Academic Performance - Makiah Makiah; Yorman Yorman; Anis Nusron (FORUM EKONOMI: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
Student learning skills improve academic success. However, gender differences and internal psychological factors play an important role in academic performance. This study aims to analyze the influence of gender and academic self-efficacy on academic performance with study program selection as a mediating variable at a private university in East Java. This study uses a quantitative approach with a cross-sectional survey design on 157 respondents selected through stratified random sampling based on gender and study programs in Management and Accounting. The data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results show that academic self-efficacy has a positive and significant effect on academic performance, while gender does not have a direct significant effect on academic performance, but it does affect study program selection. These findings indicate that internal psychological factors of students, particularly academic self-efficacy, play a more dominant role in explaining variations in academic performance than demographic factors or study program differences.